Presentation of a framework for calibrating temperature sensors - Vilela, Flávio Fraga; Rezende, Isadora Bernardo (Brazilian Journal of Production Engineering, 2025)
Metrology plays a crucial role in the standardization of measurement units, always considering uncertainty in its results, which is important at all levels of comparison. This study aimed to present and implement a framework for the calibration of temperature sensors, through the construction of two prototypes with two temperature sensors and a reference thermohygrometer. The research method was carried out in four phases: selection of materials (Phase I), assembly and validation of prototypes (Phase II and III), analysis of the collected data and proposal of a framework (Phase IV). For this study, sixty samples were collected at 1-minute intervals for comparison with the thermohygrometer. The results demonstrated that both sensors presented differences in relation to the thermohygrometer, with averages of 1.7383°C for the DHT11 and 0.8253°C for the GY-906 BCC. The calibration process was conducted through adjustment calculations in order to align the sensor measurements with the reference values. After implementing these adjustments, the calibrated prototypes were able to perform more accurate and consistent measurements. Therefore, the calibration of the aforementioned sensors through the proposed framework reduced the uncertainty of the temperature measurements.